2014
DOI: 10.1530/eje-13-0769
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mineral density is related to high physiological levels of free thyroxine in peri-menopausal women

Abstract: Objective: To determine whether thyroid hormone (free thyroxine (fT 4 )) rather than TSH is directly related to bone mineral density (BMD). Design: Cross-sectional population cohort study of peri-menopausal women. Methods: Of a sample of 6846 peri-menopausal Dutch women who participated in an osteoporosis-screening programme, a cohort of 2584 was randomly selected for the assessment of thyroid function (TSH, fT 4 and thyroid peroxidase antibodies (TPO-Abs)). TPO-Ab-positive women, with a previous history of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 27 publications
4
29
2
Order By: Relevance
“…Our study demonstrates lower bone mineral density at axial skeleton (spine and hip) in hyperthyroid perimenopausal women with Graves' disease compared to healthy controls in accordance with results of many other authors (12,13). Some studies have proved that in premenopausal women this decrease in the bone density is observed mainly in cortical bone (femoral neck) similarly to other examples of secondary osteoporosis (14).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study demonstrates lower bone mineral density at axial skeleton (spine and hip) in hyperthyroid perimenopausal women with Graves' disease compared to healthy controls in accordance with results of many other authors (12,13). Some studies have proved that in premenopausal women this decrease in the bone density is observed mainly in cortical bone (femoral neck) similarly to other examples of secondary osteoporosis (14).…”
Section: Discussionsupporting
confidence: 92%
“…In the studies of van Rijn and cols. similar association was found in euthyroid perimenopausal women -higher fT4 levels within the normal reference range were independently related to decreased BMD at lumbar spine (13).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…TSH even moderately below or above the reference range is an independent predictive factor for vertebral fractures. 13,15,[19][20][21][22] The HUNT2 study revealed a weak association between mild increase or decrease of TSH and a higher risk of hip fractures, fracture risk being evaluated on the basis of the information given by examiners during the 12.5 years of follow-up. 23 The same study described an association between TSH in the hyperthyroid range and low bone mineral density in the forearm.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous studies demonstrating the increased susceptibility of postmenopausal women to the accelerated bone loss in hyperthyroid states brought about by estrogen deficiency. (7,36,37) Hypothetically, because estradiol levels are already low, indeed lower than in men of similar age, a lowering of already strongly raised gonadotropin levels due to undertreated hypothyroidism would not exacerbate bone loss.…”
Section: Fig 2 Women Cumulative Duration Of Low Tsh (Hyperthyroid mentioning
confidence: 99%